Предмет: Алгебра, автор: MonsterLev

Упростите выражение:

2cos(pi-alpha)+(frac{sinalpha+tg}{tgalpha})^{2}-cos^{2}alpha

Ответы

Автор ответа: Quintessence
0

2cos(π-α)+(sinα+tgα/tgα)²-cos²α;

 

Пошагово:

1) 2cos(π-α)=-2cosα;

2) sinα+tgα/tgα=(sinα*cosα+sinα)/cosα/tgα=cosα+1;

 

-2cosα+(cosα+1)²-cos²α=-2cosα+cos²α+2cosα+1-cos²α=1.

 

Ответ: 1.

Автор ответа: Artem112
0

2cos(pi-alpha)+(frac{sinalpha+tgalpha}{tgalpha})^2-cos^2alpha=-2cosalpha+(frac{sinalpha}{tgalpha}+frac{tgalpha}{tgalpha})^2-cos^2alpha=-2cosalpha+(cosalpha+1)^2-cos^2alpha=-2cosalpha+cos^2alpha+2cosalpha+1-cos^2alpha=1

Похожие вопросы
Предмет: Алгебра, автор: artistas
Предмет: Русский язык, автор: abdyvalievdmitri1911